Unilateral environmental policy and offshoring - Simon J. Bolz; Fabrice Naumann; Philipp M. Richter (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2024)
Expanding on a general equilibrium model of offshoring, we analyze the effects of a unilateral emissions tax increase on the environment, income, and inequality. Heterogeneous firms allocate labor across production tasks and emissions abatement, while only the most productive can benefit from lower labor and/or emissions costs abroad and offshore. We find a non-monotonic effect on global emissions, which decline if the initial difference in emissions taxes is small. For a sufficiently large difference, global emissions rise, implying emissions leakage of more than 100%. The underlying driver is a global technique effect: While the emissions intensity of incumbent non-offshoring firms declines, the cleanest firms start offshoring. Moreover, offshoring firms become dirtier, induced by a reduction in the foreign effective emissions tax in general equilibrium. Implementing a BCA prevents emissions leakage, reduces income inequality in the reforming country, but raises inequality across countries.
urn:nbn:de:bsz:14-qucosa2-912562
Keywords: F18; F12; F15; Q58; 330; Offshoring; Emissions leakage; Environmental policy; BCA; Heterogeneous firms; Income inequality